2022
DOI: 10.1038/s41598-022-22971-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hormone therapy side effects on health-related quality of life, distress, and well-being of breast cancer survivors

Abstract: To explore the modulatory role of Adjuvant Hormone Therapy (AHT) on health-related quality of life (QoL), subjective well-being and distress prevalence in Breast Cancer (BC) survivors, considering the survival phase. Cross-sectional study with control group. 616 BC survivors participated. Examination of interaction effect between AHT and time since end of primary treatment showed that many of the positive changes observed through the survival phases were experienced exclusively by survivors without AHT. When A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Although it is difficult to establish the directionality of the relationships found and we believe that a bidirectional influence may be likely, previous studies (28,44) have shown the benefit to the HRQOL of cancer survivors of maintaining an active work life. Based on the authors' previous results (28) , being employed has a positive impact on the domains of financial problems, sexual problems, concern about appearance, social avoidance, and negative and positive affectivity. Having a job was also associated with better HRQOL in areas directly related to common side effects of cancer treatment, such as pain and fatigue.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Although it is difficult to establish the directionality of the relationships found and we believe that a bidirectional influence may be likely, previous studies (28,44) have shown the benefit to the HRQOL of cancer survivors of maintaining an active work life. Based on the authors' previous results (28) , being employed has a positive impact on the domains of financial problems, sexual problems, concern about appearance, social avoidance, and negative and positive affectivity. Having a job was also associated with better HRQOL in areas directly related to common side effects of cancer treatment, such as pain and fatigue.…”
Section: Discussionmentioning
confidence: 85%
“…These results further support the need for special consideration of this phase within early survival insofar as it constitutes a transitional phase from patient to survivor. The re-entry phase involves psychosocial and behavioral experiences more pronounced and has a greater impact on HRQOL than other phases of post-treatment survival (20,24,28,38,45) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations